2014
DOI: 10.7732/kjpr.2014.27.6.671
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships in Korean Elaeagnus L. Based on nrDNA ITS Sequences

Abstract: -Molecular phylogenetic analyses of Korean Elaeagnus L. were conducted using seven species, one variety, one forma and four outgroups to evaluate their relationships and phylogeny. The sequences of internal transcribed spacer regions in nuclear ribosomal DNA were employed to construct phylogenetic relationships using maximum parsimony (MP) and Bayesian analysis. Molecular phylogenetic analysis revealed that Korean Elaeagnus was a polyphyly. E. umbellata var. coreana formed a subclade with E. umbellata. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The topology of phylogenetic tree obtained in this study is largely consistent with previous phylogenetic study of Elaeagnaceae based on ITS sequences of nuclear rDNA, which showed that Elaeagnus glabra was clustered with Elaeagnus macrophylla , while Elaeagnus multiflora was clustered with Elaeagnus umbellate (Son et al. 2014 ). In the future, more species and more samples from each species are necessary to fully resolve the phylogeny of Elaeagnaceae.…”
supporting
confidence: 90%
“…The topology of phylogenetic tree obtained in this study is largely consistent with previous phylogenetic study of Elaeagnaceae based on ITS sequences of nuclear rDNA, which showed that Elaeagnus glabra was clustered with Elaeagnus macrophylla , while Elaeagnus multiflora was clustered with Elaeagnus umbellate (Son et al. 2014 ). In the future, more species and more samples from each species are necessary to fully resolve the phylogeny of Elaeagnaceae.…”
supporting
confidence: 90%
“…Currently, several phylogenetic studies have provided credible insights for understanding the evolutionary relationships of Elaeagnus , and the consensus trees supported the monophyletic origin of the genus Elaeagnus and Hippophae ( Bartish et al, 2002 ; Kim et al, 2020 ; Zhao et al, 2020 ). Son et al (2014) provided the molecular phylogenetic relationships of nine common Asian Elaeagnus species based on nrDNA ITS sequences. Their study reported that different clustering methods can be used for obtaining similar divergent results, except for the ambiguity in the divergence time of the outer taxa in the genera Shepherdia and Hippophae.…”
Section: Introductionmentioning
confidence: 99%
“…chloroplast genomes, has been recently sequenced [5][6][7]. Furthermore, several attempts have been made to identify species in the Elaeagnus by using DNA barcoding when determining phylogenetic relationships and describing new species [8][9][10][11]. In addition, different types of molecular markers have been developed to study genetic diversity in Elaeagnus populations [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%